Analysis Environmental Viability of Crop-Cattle Integration in Climate Vulnerable Districts of Bangladesh (SAARC Journal of Agriculture, 2026)
Low carbon farming (LCF) through crop cattle interaction has great impact on climate change. The study presents the findings of environmental viability of LCF sets through crop cattle integration under climate change shocks. Data were collected from 300 low carbon sample farms under three coastal districts of Bangladesh namely Khulna, Satkhira and Bagerhat. The carbon sequestration data were recorded under three alternate options of the treatments from Boro and Aman rice field. There were nine and five adaptation options found in the Boro and Aman rice seasons, respectively. About 27% respondent farmers adopted soil and rice crop management technique with climate stress-tolerant varieties involving ideal fertilizer management and irrigate in Boro rice season. On the other hand, about 54% responded farmers chose the adaptation option of soil and rice management involving balanced fertilizer use and irrigation. The estimated highest initiative feasibility of low carbon farm found in Dumuria upazila of Khulna district, where Boro and Aman rice yield observed 6240 kg and 4510 kg/ha along with a technical feasibility indicator of 1.25% and 1.19% of OC (organic carbon) sequestration in soil, respectively. It recommends that 50% of NPKSZn with bio-solids may be effective for low carbon farming.SAARC J. Agric., 23(2): 253-271 (2025)